Anatomy and fine structure of the alimentary canal of the spittlebug Lepyronia coleopterata (L.) (Hemiptera: Cercopoidea) - Zhong, Haiying (Ventricular Restraint Improves Outcomes in HF Patients with CRT, 2013)
The alimentary canal of the spittlebug Lepyronia coleopterata (L.) differentiates into esophagus, filter chamber, midgut (conical segment, tubular midgut), and hindgut (ileum, rectum). The filter chamber is composed of the anterior extremity of the midgut, posterior extremity of the midgut, proximal Malpighian tubules, and proximal ileum; it is externally enveloped by a thin cellular sheath and thick muscle layers. The sac-like anterior extremity of the midgut is coiled around by the posterior extremity of the midgut and proximal Malpighian tubules. The tubular midgut is subdivided into an anterior tubular midgut, mid-midgut, posterior tubular midgut, and distal tubular midgut. Four Malpighian tubules run alongside the ileum, and each terminates in a rod closely attached to the rectum. Ultrastructurally, the esophagus is lined with a cuticle and enveloped by circular muscles; its cytoplasm contains virus-like fine granules of high electron-density. The anterior extremity of the midgut consists of two cellular types: (1) thin epithelia with well-developed and regularly arranged microvilli, and (2) large cuboidal cells with short and sparse microvilli. Cells of the posterior extremity of the midgut have regularly arranged microvilli and shallow basal infoldings devoid of mitochondria. Cells of the proximal Malpighian tubule possess concentric granules of different electron-density. The internal proximal ileum lined with a cuticle facing the lumen and contains secretory vesicles in its cytoplasm. Dense and long microvilli at the apical border of the conical segment cells are coated with abundant electron-dense fine granules. Cells of the anterior tubular midgut contain spherical secretory granules, oval secretory vesicles of different size, and autophagic vacuoles. Ferritin-like granules exist in the mid-midgut cells. The posterior tubular midgut consists of two cellular types: 1) cells with shallow and bulb-shaped basal infoldings containing numerous mitochondria, homocentric secretory granules, and fine electron-dense granules, and 2) cells with well-developed basal infoldings and regularly-arranged apical microvilli containing vesicles filled with fine granular materials. Cells of the distal tubular midgut are similar to those of the conical segment, but lack electron-dense fine granules coating the microvilli apex. Filamentous materials coat the microvilli of the conical segment, anterior and posterior extremities of the midgut, which are possibly the per...